(untitled) (Revista Internacional de Folkcomunicação, 2024)
The article analyzes the content of pamphlets from cordel literature that address the life, work and death of the Brazilian singer and composer Antônio Carlos Belchior, who made himself known through the title of his highly successful song Apenas um rapaz latino-americano. The analysis is carried out using eight criteria: childhood, youth and beginning of a career; latinity and music; and disappearance, absolution and legacy. It accepts the hypothesis that the aforementioned leaflets present the artist with characteristics similar to those of characters in traditional narratives of cordel literature, to the detriment of the socially constructed image of the Latin American boy. Preliminarily, it discusses aspects related to Belchior’s work, image and intended Latinity.